"Thinking Outside the Camp": Education Solutions for Syrian Refugees in Jordan. Issue 1 (18th January 2018) - VON BAEYER, SARAH LEBARON
Abstract : This paper presents a case study of a project on education solutions for Syrian refugees in Jordan conducted between 2015–2017. First, it describes how ReD's methodological approach provided a unique perspective to studies on refugees. By immersing a team in the day‐to‐day lives and settings that most Syrian refugees experience in Jordan—i.e., outside of camps and in people's actual homes—ReD led its client to "think outside the camp, " something that relief agencies and companies often fail to do due to the refugee camp model of humanitarian assistance that, ever since WWII, has dominated the approach to refugees. Second, as a result of its unique methodological approach, ReD uncovered important findings about social networks and technology use and access in Syrian refugees' homes and communities that ultimately shaped the client's perspective on solution development. For example, ReD's team of ethnographers found that nearly all out‐of‐camp Syrian households had at least one Smartphone in their possession, if not two or more, and that digital devices served as important tools of communication and community‐building among people displaced by conflict. Consequently, ReD advised its client to tap into these pre‐existing social networks and mobile technologies in order to develop an education solution that best fit refugees' "real‐life" practices. Ultimately, both ReD's methods and its findings led to a significant impact in how the client strategized on and developed their education solution, and can serve as a broader model for how to approach building services and/or products for displaced populations with access to basic mobile technologies. "The Jordanian educational/policy response to refugees is broken and will not easily be fixed or tinkered with. Solutions must work around this system." (Education expert and activist working with vulnerable youth and school dropouts in Jordan)